2014
DOI: 10.1103/physrevc.90.054324
|View full text |Cite
|
Sign up to set email alerts
|

Resonances inC14observed in theHe4(10

Abstract: The α( 10 Be, α) 10 Be resonant scattering reaction has been measured at nine 10 Be beam energies from 25 to 48 MeV, scanning out resonances in 14 C from excitation energies of 13 to 24 MeV. Angular distribution measurements were used to assign the spin and parity of 5 − to resonances at E x = 18.82(2) and 19.67(2) MeV and 6 + at E x = 20.80(2) MeV. The data also strongly indicate a 3 − resonance at 17.32(2) MeV. The systematic uncertainty on the excitation energies is 175 keV. An R-matrix analysis has been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 21 publications
5
50
0
Order By: Relevance
“…The first band, which we call a π -bond linear chain, has two valence neutrons in a π orbit and is built on the 0 + state at 14.6 MeV which is just above the α + 10 Be threshold but below the 2α + 6 He threshold. It was found that the energies and widths of the resonances observed by the α + 10 Be elastic scattering [36,37] qualitatively agree with the theoretical calculations [15,18] including ours. Therefore, they are regarded as the π -bond linear-chain candidates, although the experimental spin-parity assignment was somewhat ambiguous.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…The first band, which we call a π -bond linear chain, has two valence neutrons in a π orbit and is built on the 0 + state at 14.6 MeV which is just above the α + 10 Be threshold but below the 2α + 6 He threshold. It was found that the energies and widths of the resonances observed by the α + 10 Be elastic scattering [36,37] qualitatively agree with the theoretical calculations [15,18] including ours. Therefore, they are regarded as the π -bond linear-chain candidates, although the experimental spin-parity assignment was somewhat ambiguous.…”
Section: Introductionsupporting
confidence: 77%
“…Yamaguchi et al [39] reported the result of the α + 10 Be elastic scattering and updated the information about the candidates of the π -bond linear chain. Although the spin-parity assignments for several states are not consistent with those found in previous experiments [35][36][37]39], they first observed a candidate of the bandhead of the linear chain (J π = 0 + ), which should be compared with theoretical calculations. The other experiment was reported by Tian et al [40] and Li et al [41] who observed the resonances populated by the 9 Be( 9 Be,α + 10 Be)α reaction.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations